The complaints - Rankin, Ian. (New York : Little, Brown and Co., 2011)
Internal-affairs detective Malcolm Fox finds an investigation into fellow cop Jamie Breck becoming even more dangerous when a murder takes place far too close to home.
"A Reagan Arthur book."
"Originally published in Great Britain by Orion, September 2009"--T.p. verso.
Lariat Reading List, TLA 2012
Keywords: Police -- Scotland -- Edinburgh -- Fiction; Police internal investigation -- Fiction; Edinburgh (Scotland) -- Fiction; Mystery fiction